Raffaele Riario, Jacopo Galli, and Michelangelo’s Bacchus, 1471–1572 - Christian, Kathleen W. (AU) (Harvey Miller, 2025)
On Michelangelo's first day in Rome, in June 1496, Cardinal Raffaele Riario asked him if he could create ‘something beautiful'in competition with the antique. The twenty-one-year old sculptor responded to this unique challenge with the statue of Bacchus now in the Bargello museum. This statue, as well as the Sleeping Cupid which first brought Michelangelo to Riario's attention, have long been shrouded in mystery, and the Bacchus as well as its patron have long suffered from critical censure.Through a comprehensive analysis of overlooked and previously-unpublished sources, this study sheds new light on the Sleeping Cupid, the Bacchus,and a fascinating period in the history of Renaissance Rome when the careers of Riario, Galli, and Michelangelo were closely intertwined. It considers the rise of the Riario dynasty starting with the election of Pope Sixtus IV in 1471, Riario's partnership with Jacopo Galli in the reconstruction of the palace now known as the Palazzo della Cancelleria, the attempted sale of Michelangelo's Sleeping Cupid in Rome as an antiquity, Riario's patronage of the Bacchus, and the Bacchus's displayin the house of the Galli up until its sale to the Medici in 1572. Taking a broad, interdisciplinary perspective, it offers a fundamental reassessment of Cardinal Riario's career as a patron, of Jacopo Galli's role as an intermediary for both Riario and Michelangelo, and of Michelangelo's collaboration with Riario and Galli.